Significance of 4D US parameters for the clinical treatment of female patients with stress urinary incontinence - Jiang, Changqin; Zhang, Song; Chen, Jing; Zhang, Yangyang; Cai, Keke; Chen, Wei; Wu, Yuanyuan; Liang, Chaozhao (Frontiers in Surgery, 2023)
Background: Stress urinary incontinence which has been associated with abnormal pelvic floor muscle function or morphology is a common condition. This research aims to evaluate the role of 4D pelvic floor ultrasound on the postoperative complication of transobturator suburethral tape (TOT) in female patients with SUI. Methods: We enrolled 53 women with stress urinary incontinence (SUI). Before transobturator suburethral tape (TOT) procedures, the patients underwent 4D pelvic floor ultrasonography. The measurements include residual urine volume, bladder detrusor thickness in resting state, the vertical distance from the bladder neck to the posterior inferior edge of pubic symphysis at rest and Valsalva movement, posterior angle of bladder urethra and urethral rotation angle. The degree of movement of the bladder neck (the difference between the vertical distance from the bladder neck to the posterior inferior edge of the pubic symphysis under the resting state and the maximum Valsalva movement) and the formation of a funnel at the internal orifice of the urethra were calculated. Results: Mean bladder detrusor thickness was 2.6 ± 0.9 mm, the vertical distance from the bladder neck to the posterior inferior edge of pubic symphysis was 27.7 ± 4.5 mm, posterior angle of the bladder was 122.7 ± 18.9°, the vertical distance from rectal ampulla to the posterior inferior edge of pubic symphysis was 18.5 ± 4.6 mm, and the mean area of hiatus of the levator ani muscle was 22.1 ± 6.0 cm2. Preoperative ultrasound measurements during the Valsalva movement were summarized in Table 3. The mean posterior angle of the bladder on Valsalva was 159.3 ± 23.1° and mean urethral rotation angle was 67.2 ± 21.4°. Conclusions: 4D pelvic floor ultrasound is a reliable method in evaluating preoperational morphological characteristics of patients with SUI. These datasets could help with reducing complications’ incidence associated with TOT procedures.